PENGARUH TEKNIK ICE BREAKING TERHADAP HASIL BELAJAR SISWA KELAS VIII (DELAPAN) PADA MATA PELAJARAN PAI DI SEKOLAH SMPIT BOEDI LUHUR BEKASI - Afan Riziq Al-Saleh; Irham Irham (Turats, 2022)
This study aims to determine student learning outcomes in PAI subjects in class VIII (eight) at SMPIT Boedi Luhur Bekasi. This research is a quantitative research using descriptive statistical data analysis, which aims to determine how student learning outcomes in PAI subjects in class VIII (eight) at SMPIT Boedi Luhur Bekasi School. The population in this study amounted to 71 students from all grades VIII 1 to class VIII 3, and the sample used was class VIII 2 and VIII 3 SMPIT Boedi Luhur Bekasi, which amounted to 25 students from class VIII 2 and class VIII 3, totaling 23 with a total of 48 samples. Sampling using a random sampling technique with a true experimental design. The result of this study strengthens the previous hypothesis, which shows that the null hypothesis (H0) is a hypothesis that states that there is no relationship between the X and Y variables. The alternative hypothesis (Ha) is a hypothesis that states that there is a relationship between X and Y variables that has a significant effect. Between ice-breaking technique and PAI learning outcomes. So the result of this study have an average value / mean = 82.52, median = 83.00, mode = 84, standard deviation / frozen side = 2.485 minimum value = 76, maximum value = 86, with PAI learning outcomes (variable Y) has a mean value = 82.00, median = 83.00, mode = 84, standard deviation / freezing deviation = 4,167, minimum value = 73, maximum value = 88, obtained from linear regression calculations. This is proven by the t number of 10.262. In other words, there is an influence between the ice-breaking technique on PAI learning outcomes.